(untitled) (Al-Mansour Journal, 2022)
In this paper, first, the Golomb’s postulates of randomness are expanded to construct a good mathematical base, and then expand the binary standard randomness tests to be suitable to be applied on penta-sequences this mean the elements of the sequence belong to Galois Field GF(5). Second we will show usefulness of using penta-sequences in cryptography. The paper also includes some tables describe the tests results of the penta-sequences generated from some digital generators, like the Multiplicative Cyclic Group System (MCGS). The proposed cryptosystem using the GF(5)-sequences will compress or minimizing the ciphertext size comparing with the cryptosystems using GF(2)-sequences.